Self-assembly and guest-induced disassembly of triply interlocked [2]catenanes. Issue 24 (24th February 2021) - Zhang, Ying-Ying; Qiu, Feng-Yi; Shi, Hua-Tian; Yu, Weibin
Abstract : Two triply interlocked [2]catenanes and one simple metallacage were constructed by tuning the widths of the organometallic dinuclear building blocks, and the interlocked architectures were disassembled by large aromatic molecules. Abstract : Two fascinating triply interlocked [2]catenanes and one simple triangular prism metallacage were constructed by tuning the widths of the organometallic dinuclear building blocks. Notably, the interlocked architectures were disassembled in the presence of large aromatic molecules to form their corresponding monomeric host–guest complexes.